Biomaterials and Oxygen Join Forces to Shape the Immune Response and Boost COVID‐19 Vaccines. Issue 18 (20th July 2021) - Colombani, Thibault; Eggermont, Loek J.; Rogers, Zachary J.; McKay, Lindsay G. A.; Avena, Laura E.; Johnson, Rebecca I.; Storm, Nadia; Griffiths, Anthony; Bencherif, Sidi A.
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has led to an unprecedented global health crisis, resulting in a critical need for effective vaccines that generate protective antibodies. Protein subunit vaccines represent a promising approach but often lack the immunogenicity required for strong immune stimulation. To overcome this challenge, it is first demonstrated that advanced biomaterials can be leveraged to boost the effectiveness of SARS‐CoV‐2 protein subunit vaccines. Additionally, it is reported that oxygen is a powerful immunological co‐adjuvant and has an ability to further potentiate vaccine potency. In preclinical studies, mice immunized with an oxygen‐generating coronavirus disease 2019 (COVID‐19) cryogel‐based vaccine (O2 ‐CryogelVAX ) exhibit a robust Th1 and Th2 immune response, leading to a sustained production of highly effective neutralizing antibodies against the virus. Even with a single immunization, O2 ‐CryogelVAX achieves high antibody titers within 21 days, and both binding and neutralizing antibody levels are further increased after a second dose. Engineering a potent vaccine system that generates sufficient neutralizing antibodies after one dose is a preferred strategy amid vaccine shortage. The data suggest that this platform is a promising technology to reinforce vaccine‐driven immunostimulation and is applicable to current and emerging infectious diseases. Abstract : Cryogels loaded with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) nucleocapsid (N) and receptor‐binding domain (RBD) proteins (antigens), CpG (adjuvant), and GM‐CSF (immunomodulatory factor) activate both arms of the adaptive immune system. Additionally, oxygen, used as a co‐adjuvant, boosts the production of binding/neutralizing antibodies against the virus. This advanced biomaterial offers a new avenue to reinforce vaccines against infectious diseases.